Decentralization, Local Governance, and Localizing the Sustainable Development Goals in Asia and the Pacific - Bruno Carrasco; Hanif A. Rahemtulla; Rainer Rohdewohld (Routledge, 2023)
Since its adoption in 2015, the 2030 Agenda on Sustainable Development has shaped not only international development cooperation but also the design of national trajectories for social and economic development. In tandem with other global agendas adopted that year (such as the Paris Agreement on Climate Change and UN Habitat's New Urban Agenda) it remains the global and regional blueprint for sustainable development despite the COVID-19 pandemic. The term ""localizing the Sustainable Development Goals (SDGs)"" has been used to capture the importance of subnational governments for achieving national SDG agendas. However, there is little deeper analysis of the required nexus between fiscal, political, and legal arrangements for SNGs; their involvement in national policy arenas (which discuss and decide on national SDG strategies); and the need for locally disaggregated data systems on the one hand, and effective SDG localization strategies on the other hand. It is this aspect which the present publication explores in greater detail by using country examples and conceptual analyses. The text will be of interest to policymakers, scholars, students and practitioners in public policy and public administration, decentralization, and sustainable development, with a focus on the Asia and Pacific region.
Keywords: 320; decentralization; grand challenges; local governance; policy integration; sustainable development goals